Biometria e conservação de sementes e influência do fósforo no crescimento inicial de mudas de Camu-camu (Myrciaria dubia (Kunth) McVaugh) - Nascimento, Cássia Rejane do (2014)
The Camu-camu is a species that has aroused the interest of the industry due to their nutraceutical characteristics, especially the high content of vitamin C. Although several studies, there are still gaps in our knowledge about the mechanisms involved in the physiological processes of the seed, especially those associated with storage, germination and early seedling development. In this context, the objective was to study the conservation and germination of camu-camu and the influence of phosphorus on the growth of seedlings. For this, there were three studies to: 1) determine the biometric, physical characteristics and the vigor seed of camu-camu; 2) assess the conservation and germination of camu-camu, as well as to characterize the water absorption of seeds and classified by size; 3) evaluate the initial growth of camu-camu subjected to different doses of phosphorus in different times of applications. The average results for width, thickness, length, individual mass, volume, weight of thousand seeds and number of seeds per pound were respectively: 12.04 x 15.54 x 5.54 mm, 0.79 g, 1035.77 mm3 , 734.27 g and 1362 for small seeds; 12.90 x 17.42 x 6.11 mm, 1.11 g, 1371.98 mm3, 943.67 g and 1061 for medium seeds; 14.42 x 19.14 x 6.74 mm, 1.45 g, 1859.47 mm3, 1213.70 g and 825 for large seeds. The seed size has direct correlation with the force, because the large seeds have greater vigor. Camu-camu seeds stored in cold storage at 15°C inside a plastic packaging have greater force, depending on the electrical conductivity and the speed of emergency. Camu-camu seeds immersed in water, inside the package in both environments camu-camu keep force, with emergency above 80% for 300 days of storage. Camu-camu seedlings not respond to different phosphorus doses up to 120 days form. After120 days, the fertilization needed for better initial growth corresponding to the range 130.00 to 187.00 mg P dm-3 of soil up to 180 days.